Why Europe? The Rise of the West in World History, 1500–1850 (an excerpt) (translated by Michael Rudakov) - Jack А. Goldstone (Journal of Economic Sociology, 2013)
In his book “Why Europe? The Rise of the West in World History, 1500–1850”, famous sociologist and political scientist Jack Goldstone explores how Europe managed to get from a peripheral and lagging district into the area with great innovations, wealth and mighty power. What were the reasons for that? Was the springtime of Europe generated from its unique life course? Was it caused by changesin relationships between Europe and the rest of the world? How dissimilar was thistransformation to other golden ages of human history? There are not so many historians who can offer better answers to the above issues than Jack Goldstone,who has studied them for several decades. In his book, he relies on recent research findings in the field and presents the worldwide audience fundamental arguments written in plain language.The journal “Economic Sociology” publishes an excerpt Jack Goldstone’s book —“Conclusion. The Rise of the West: A Temporary Phase?”, where the authorsingles out six factors and argues that their specific combination produced the Europe’s success. Alongside this Goldstone considers backgrounds for modern economic growth formed by accumulation of technical and economic achievements under conditions of the world competition. Moreover, the author offers the primary reasons why economic growth did not spill over into more nations; they include lack of scientific background and entrepreneurial opportunity. Finally, Goldstone tries to read the nearest future and to indicate the potential for the world progress in the coming decades.